Investigating the reaction mechanisms and structural enhancements in maraging steel 300 reinforced with in-situ TiC+TiB2 via laser powder bed fusion - Soni H.; Sharma P.; Sahoo B.N. (My University, 2025)
This study utilizes a hybrid process combining mechanical ball milling and Laser Powder Bed Fusion (LPBF) to fabricate in-situ TiC–TiB2 reinforced Maraging Steel 300 (MS300) composite with addition of Ti and B4C particles. The reaction mechanism between MS300 and Ti and B4C particles has been established to produce in-situ TiC + TiB2 in both theoretically and experimentally. MS300 acts as an intermediate, facilitating the formation of TiC and TiB2 from Ti and B4C at a lower temperature than when these materials are heated separately. This study reveals that base MS300 alloy exhibits an average grain size of 5.205 μm with a cellular grain structure, while the in-situ composite shows significant grain refinement to .945 μm due to pinning effect of in-situ reinforcement. Comparative analysis reveals that substantial mechanical properties enhanced in the in-situ composite, including a 32 % increase in ultimate tensile strength, 9 % increase in yield strength, and 36 % improvement in hardness. Post-solution treatment regains ductility of 20 % and 60 % for the base and composite materials, respectively. The simultaneous enhancement of strength and ductility is attributed to the combined effects of in-situ reinforcement and grain refinement achieved through LPBF process. The composite material also shows weaker crystallographic orientation intensity compared to base sample (8.092 vs. 14.407). The enhancement in strength has been established through various strengthening mechanisms. © 2025 Elsevier B.V.